Cinta Rasul dalam Grebeg Tahu: Studi Tradisi Perayaan Maulid Nabi di Desa Sumbermulyo, Kabupaten Jombang: Love for the Apostle in Grebeg Tahu: Study of the Mawlid Nabi Ceremonial Tradition in Sumbermulyo Village, Jombang Regency - Huda, Imam Walid Asrofuddin Ulil; Farikhah, Farikhah (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
Mawlid Nabi is a tradition that has been maintained for decades which experienced developments and innovations by generations. Based on various economic, social, and cultural factors, there are new creations of this traditional ritual resulting from creativity to express love toward the Prophet Muhammad such as Grebeg Tahu as practiced by the people of Sumbermulyo Village, Jogoroto District, Jombang Regency, East Java Province of Indonesia. By inquiring what is the social, cultural, and economic background and how was the new tradition developed, also what is its impact, the authors used the phenomenological method and reinforced it with an anthropological approach. Besides, the Hobsbawm theory of traditional invention was also used as the analytical tool. This study is then indicative that the Sumbermulyo community has a socio-cultural background as Sunni, Nahdiliyin, followers who have had a long tradition of Maulid Nabi. Besides, as most of them are are MSE entrepreneurs in tofu industry, therefore it was what they used to develop the unique ritual of Grebeg Tahu. Finally, this new tradition has proven to have had various impacts on social, cultural, and economic aspects, as well as from a religious perspective